Surgical outcomes of patients with non-small cell lung cancer following neoadjuvant treatment - ERMERAK, NEZİH ONUR (MARMARA UNIV, FAC MEDICINE, 2018)
Objective: Although, anatomical resection of non-small cell lung cancer (NSCLC) following neoadjuvant therapy is still controversial, it is a widely accepted approach for thoracic surgery practice. The aim of this study is to briefly evaluate clinical results, long term survival, and factors affecting survival of the patients with locally advanced NSCLC, pancoast tumour and lung cancer with solitary brain metastasis, who have been operated at our institution following neoadjuvant therapy. Materials and Method: Between March 2006 and March 2012, 70 patients with NSCLC diagnosis who underwent anatomic pulmonary resection following neoadjuvant therapy were included in the study. Results: A three year survival (39%) and a 5-year survival (29%) were 16 +/- 6.8 and 37 +/- 9.89 months, respectively. The mean survival was found to be 37.15 +/- 3.06 months. When survival rate was evaluated according to localization of tumor, it was lower in central and left upper lobe tumors compared to other anatomical localizations (P=0.042). The mean 5-year survival times were 50.00 +/- 5.65 months in stage 0 patients, 35.39 +/- 5.85 months in stage 1 patients, 37.40 +/- 6.89 months in stage 2 patients and 21.44 +/- 3.10 months in stage 3 patients. Conclusion: We can achieve significant survival results by the anatomical pulmonary resection following neoadjuvant therapy.
Keywords: Non-small cell lung cancer; Neoadjuvant therapy; Chemotherapy; Radiotherapy; Surgery; INDUCTION CHEMOTHERAPY; STAGE; IIIA; SURVIVAL; THERAPY; PNEUMONECTOMY; MORBIDITY; MORTALITY; RESECTION; SURGERY